The Upregulation of Carnitine Palmitoyltransferase 1a (CPT1a) Expression under Prolonged Fasting in CD36 Knockout Mice - Mirasari Putri; Mas Rizky A.A. Syamsunarno; Tatsuya Iso; Masahiko Kurabayashi (Global Medical & Health Communication (GMHC), 2018)
Food deprivation is one of the extreme conditions that mammals have to survive. The majority of the tissues, excluding the brain and red blood cells, depend on the fatty acids (FA) utilization to produce energy. We recently showed in mice lacking for CD36 (CD36−/−), the uptake of FA is limited with dramatically increased of glucose uptake in heart and skeletal muscle in fasted condition, indicating a compensatory mechanism of organ to fulfill an energy demand. The liver is the central tissue maintaining metabolic homeostasis in fasted state. Synthesize adenosine triphosphate (ATP) in the mitochondria via beta-oxidation was mediated by carnitine palmitoyltransferase 1a (CPT1a). The objective of this research was to explore the role of CD36 in CPT1a expression in the fasted state. This research was conducted at Gunma University Japan in 2015. The method was in vivo-experimental, that we used CD36−/− and wild-type (WT) mice, as a control. The gene expression of CPT1a was measured by real-time PCR. Fasting condition up regulated mRNA expression of CPT1a in both WT and CD36−/− mice in 24 h and 48 h. However in CD36−/− mice, the mRNA expression of CPT1a in 24 h fasted state was lower very significantly than WT mice (p<0.01). We demonstrate that CD36 deficiency up regulate CPT1a gene expression, suggested that CD36 is essential for nutrient homeostasis when requirement for FA is increased and obtainability of nutrient is inadequate. PENINGAKTAN EKSPRESI GEN CARNITINE PALMITOYLTRANSFERASE 1A (CPT1A) PADA CD36 KNOCKOUT MICE DALAM KEADAAN PUASAKekurangan makanan adalah salah satu kondisi ekstrem yang harus dihindari oleh mamalia. Sebagian besar jaringan, kecuali otak dan sel darah merah sangat bergantung pada pemanfaatan langsung asam lemak untuk menghasilkan energi. Penelitian kami sebelumnya menunjukkan pada mencit dengan defisiensi CD36 (CD36−/−), serapan asam lemak terbatas karena peningkatan pengambilan glukosa hati dan otot rangka secara signifikan dalam kondisi puasa yang mengindikasikan mekanisme kompensasi organ untuk memenuhi kebutuhan energi. Hati adalah jaringan sentral yang menjaga homeostasis metabolik tubuh dalam keadaan berpuasa. Sintesis adenosine triphosphate (ATP) di mitokondria melalui beta-oksidasi dimediasi oleh carnitine palmitoyltransferase 1a (CPT1a). Tujuan penelitian ini mengetahui peran CD36 dalam ekspresi CPT1a dalam keadaan puasa. Penelitian ini dilakukan di Universitas Gunma Jepang pada tahun 2015. Metode penelitian ini adalah eksperimental in vivo dengan menggunakan mencit CD36−/− dan wild type (WT) sebagai kontrol. Ekspresi gen CPT1a diukur dengan real-time PCR. Puasa meningkatkan ekspresi mRNA CPT1a pada mencit WT dan CD36−/− baik setelah puasa selama 24 jam dan 48 jam. Namun, pada mencit CD36−/−, ekspresi mRNA CPT1a dalam keadaan setelah dipuasakan 24 jam lebih rendah daripada mencit WT (p<0,01). Penelitian ini menunjukkan bahwa defisiensi CD36 mengatur ekspresi gen CPT1a sehingga CD36 sangat diperlukan untuk homeostasis nutrisi ketika kebutuhan asam lemak meningkat dan kemungkinan ketersediaan nutrisi terbatas.